Safety of Underground Coal Mine Using Artificial Intelligence and Wireless Sensor Network (International Journal of Engineering and Computer Science, 2016)
Mining process plays the vital role in the modern era for the development of nation as well as the world wide. By using the mining only we can now a day’s having so many essential goods what we are using everywhere[2]. If we take the case of coal,  then it is the most important product through which all the byproduct we are getting like fuel, wax, plastic, peat etc. In this paper  purpose was to provide an implementable design scenario for underground coal mines using Artificial intelligence technique along with wireless sensor networks (WSNs)[1]. The main reason being that given the intricacies in the physical structure of a coal mine, only low power WSN nodes can produce accurate surveillance and accident detection data[4,6]. Because of the rapid growth of accident in mines area like roof fall, explosion, etc, the development of intelligent sensors, microcontrollers, and network technology, became essential; so as to make a reliable condition for our automatic real-time monitoring of coal mine[2]. The underground system collects temperature, humidity and methane values of coal mine through these intelligent sensor nodes in the mine, and provide the necessary safety prerequisite to avoid accidents.